A new technique for the synthesis of lanthanum substituted nickel cobaltite nanocomposites for the photo catalytic degradation of organic dyes in wastewater - Muhammad Ayyob; Iqbal Ahmad; Fiaz Hussain; Muhammad Kashif Bangash; Javeed A. Awan; Jean-Noël Jaubert (Arabian Journal of Chemistry, 2020)
Developing cost-effective and more efficient nanocatalysts for the treatment of organic pollutants from process industry is always challenging for the researchers working in the field of chemistry, chemical, energy and environment engineering. In this work, a cost-effective and more efficient nanocatalysts, i.e., Nickel Cobaltite nanocomposites and its Lanthanum (La) doped derivatives with controlled surface morphology has been synthesized at 393.15 K through single step sol–gel method. The surface morphology, chemical composition, and crystal structure of the synthesized nanocomposites were analysed by scanning electron microscopy (SEM), Fourier transformed infrared spectroscopy (FTIR), and X-rays diffraction (XRD), respectively. The rough surface and well-crystallized metallic nanocomposites confirm the successful synthesis of nanocatalysts. The molar ratio of Lanthanum to Cobalt (Lax:Coy) showed a significant influence on the surface morphology and catalytic activity (Kapp = 0.15–0.47 min−1) of the products. Synthesized nanocomposites showed high catalytic activity for the reduction of methylene blue under solar irradiation. Photocatalytic results for the reduction of methylene blue show that the catalytic activity of synthesized nanocatalysts increases with the increase in the doping concentration of Lanthanum.